Effects of dietary supplementation with radix hedysari on pr oduction performance and antioxidant capacity of sheep - Xin, JZ; Liu, S (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to investigate the effects of dietary supplementation with Radix hedysari (RH) on the growth performance, slaughter performance, activity of antioxidant enzyme, and lipid metabolite of sheep. Forty 140-day-old Duhan hybrid ewe were selected and randomly allocated into four groups. Four dietary treatments were used: (1) basal diet without supplementation (Control), (2) basal diet supplemented with 1% RH, (3) basal diet supplemented with 3% RH, and (4) basal diet supplemented with 10% RH. The diets were fed for 75 d, consisting of 10 d for adaptation followed by 65 d of experimental observation. Treatment did not significantly influence ADFI, ADG and FCR. Dietary supplementation with higher RH (3%, 10%) significantly (P < 0.05) increased the dressing percentage and net meat weight, and significantly (P < 0.05) decreased the omental and perirenal adipose tissue percentage. The 10% RH treatment significantly (P < 0.05) increased antioxidant enzyme activities in samples and decreased the content of malondialdehyde (MDA) in samples. The addition of higher RH also decreased significantly (P < 0.05) the concentration of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) in samples, and increased the content of HDL-C significantly (P < 0.05). Sheep fed RH had more C18:1n9, C18:3n3, MUFA, and UFA, and a higher PUFA/SFA ratio in LD and omental adipose tissue (OAT) than animals in CON. Together, these results suggest that RH has a positive effect on the slaughter performance, antioxidation, lipid metabolite of Duhan hybrid sheep, and is also conductive to providing healthy and nutritious high-quality livestock products.